2022
DOI: 10.3892/mmr.2022.12733
|View full text |Cite
|
Sign up to set email alerts
|

Immature granulocytes: Innovative biomarker for SARS‑CoV‑2 infection

Abstract: Immature granulocytes (IGs) include metamyelocytes, myelocytes and promyelocytes, and are the precursors of neutrophils. Increased IG counts found in peripheral blood indicate an enhanced bone marrow activity. In addition, IGs have been evaluated in numerous clinical conditions, such as severe acute pancreatitis, systemic inflammatory response syndrome and infectious complications following open-heart surgery under cardiopulmonary bypass. Neutrophils are considered to play a crucial role in the host defense du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
19
0
3
Order By: Relevance
“…IG are neutrophil precursors including metamyelocytes, myelocytes, and promyelocytes and high IG values indicate an enhanced bone marrow activity. 10 , 11 It has been previously investigated as a prognostic inflammatory parameter in sepsis, acute respiratory distress syndrome, pancreatitis, coronavirus disease 2019 (COVID-19). 11 13 Kong et al 14 found that immature granulocytes were associated with early mortality in PE.…”
Section: Discussionmentioning
confidence: 99%
“…IG are neutrophil precursors including metamyelocytes, myelocytes, and promyelocytes and high IG values indicate an enhanced bone marrow activity. 10 , 11 It has been previously investigated as a prognostic inflammatory parameter in sepsis, acute respiratory distress syndrome, pancreatitis, coronavirus disease 2019 (COVID-19). 11 13 Kong et al 14 found that immature granulocytes were associated with early mortality in PE.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the existence of monoallelic vs. biallelic ACE2 and Toll-like receptor 7 genes on the X chromosome may help to explain the greater risk of COVID-19 infection in males compared to females (37). Several studies have reported laboratory parameters, such as eosinophils, lymphocytes, PLTs, immature granulocytes, ferritin and liver enzymes as biomarkers of poor outcomes in patients with COVID-19 (36,(38)(39)(40)(41)(42). Of note, only a few studies have evaluated laboratory data as biomarkers of poor outcomes in tocilizumab-treated patients with COVID-19 (29)(30)(31)(32)(33)(34)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19, the imbalance of the immune response and excessive inflammation is a major component of its pathogenesis (9). Several immune and inflammatory indicators, including the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, eosinophil-to-lymphocyte ratio, immature granulocytes, ferritin, fibrinogen, C-reactive protein, interleukin (IL)-6 and lactate dehydrogenase, have been shown to be associated with disease severity and mortality in patients with COVID-19 (10)(11)(12)(13)(14).…”
Section: Onodera's Prognostic Nutritional Index: Comparison Of Its Ro...mentioning
confidence: 99%